Etude Géotechnique Et Modélisation Volumique Des Zones Instables ; Processus D’effondrement De La Falaise Adjacente À La Voie De Contournement Du Port d’Al Hoceima (Rif, Maroc) - Labriki, Allal; Chakiri, Saïd; Nouaim, Wafae; Allouza, Mohamed; Bejjaji, Zohra; Ezzayani, Jamil (European Scientific Journal, ESJ, 2017)
Al Hoceima region (northern Morocco) is an area mostly affected by the instability of the terrain, many rockslides and landslides which occurs regularly. The last of which took place in 2011 in some part of Al Hoceima. The objective of this study is to try to understand the process and the collapse mechanisms of this area. The analysis of the geotechnical data, using a volumetric field model, makes it possible to determine the spatial variations of the parameters controlling the stability. This, thus, helps to determine the passage mechanisms of this slope from the stable state to the state of movement. The study showed that the flow of water in a loose medium and the anthropogenic impacts on the general modification of this flow is the main triggering factor. This is in addition to the anisotropy of the schistose formations that guides the flow Shear fracture along the bedding and fracture planes.